2004
DOI: 10.1158/1078-0432.ccr-1132-03
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Adhesion Molecule (KSA) Expression

Abstract: Purpose: Epithelial cell adhesion molecule (EpCAM) is a widely expressed adhesion molecule in epithelial cancers. The purpose of this study is to determine the protein expression patterns of EpCAM in renal cell carcinoma (RCC) using tissue arrays linked to a clinicopathological database to evaluate both its predictive power in patient stratification and its suitability as a potential target for immunotherapeutic treatment strategies.Experimental Design: The University of California, Los Angeles kidney cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
78
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 55 publications
5
78
0
2
Order By: Relevance
“…Epithelial cell adhesion molecule upregulation was an independent marker for poor survival in lymph node positive breast cancers , and gall bladder cancers (Varga et al, 2004). In contrast, improved survival was found associated with Ep-CAM upregulation in clear cell renal cell carcinoma (Kim et al, 2004;Seligson et al, 2004;Went et al, 2005), and gastric cancers (Songun et al, 2005). Here, we observed that survival of patients in the subgroup of moderately differentiated colon cancers also showed a significant positive correlation with Ep-CAM expression.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Epithelial cell adhesion molecule upregulation was an independent marker for poor survival in lymph node positive breast cancers , and gall bladder cancers (Varga et al, 2004). In contrast, improved survival was found associated with Ep-CAM upregulation in clear cell renal cell carcinoma (Kim et al, 2004;Seligson et al, 2004;Went et al, 2005), and gastric cancers (Songun et al, 2005). Here, we observed that survival of patients in the subgroup of moderately differentiated colon cancers also showed a significant positive correlation with Ep-CAM expression.…”
Section: Discussionmentioning
confidence: 50%
“…In breast and gall bladder cancer, patients with high Ep-CAMexpressing primary tumours indeed showed a decreased survival (Gastl et al, 2000;Spizzo et al, 2002;Spizzo et al, 2004;Varga et al, 2004). In clear cell renal cell carcinoma, Ep-CAM expression is infrequent, but patients with Ep-CAM overexpressing tumours show a trend to better survival (Kim et al, 2004;Seligson et al, 2004;Went et al, 2005). A similar correlation was reported for gastric cancers (Songun et al, 2005).…”
mentioning
confidence: 53%
“…Some reported it was a good prognostic factor in renal cell carcinoma (Seligson et al, 2004), gastric cancer (Songun et al, 2005) and esophageal cancer (Kimura et al, 2007); while a poor prognostic factor in breast cancer (Gastl et al, 2000;Schmidt et al, 2008), gallbladder cancer (Varga et al, 2004) and esophageal cancer (Stoecklein et al, 2006). The significance of Ep-CAM expression in pancreatic cancer H Akita et al…”
Section: Discussionmentioning
confidence: 99%
“…There are some clinical reports about the relation of Ep-CAM expression to the prognosis, but the significance is uncertain; high-Ep-CAM expression was described as a good prognostic factor (Seligson et al, 2004;Songun et al, 2005;Kimura et al, 2007), while in some reports highEp-CAM expression led to poor prognosis (Gastl et al, 2000;Varga et al, 2004;Stoecklein et al, 2006). Following this discrepancy, Ep-CAM may have a different role in each type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The epithelial cell adhesion molecule EpCAM (EpC) is expressed on many epithelia (1, 2) and its expression is frequently increased in nearly all carcinomas as well as myelomas (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Depending on the tumor type, high EpC expression correlates with tumor grading and/or tumor-nodemetastasis staging and/or decreased overall and poor diseasefree survival (4,5,13,14).…”
Section: Introductionmentioning
confidence: 99%